Catalytic co-pyrolysis of cellulose and linear low-density polyethylene over MgO-impregnated catalysts with different acid-base properties - Ryu, Hae Won; Tsang, Yiu Fai; Lee, Hyung Won; Jae, Jungho; Jung, Sang Chul; Lam, Su Shiung; Park, Eun Duck; Park, Young Kwon (Chemical Engineering Journal, 2019)
Various MgO impregnated catalysts were used for the catalytic co-pyrolysis (CCP) of cellulose and linear low-density polyethylene (LLDPE) at 600 °C in ambient pressure. Micro reactor-gas chromatography, a semi-batch reactor, was used as a reactor and gas chromatogram/mass spectrometry/flame ionization detector were used for product detection. Three kinds of MgO impregnated catalysts, MgO/Carbon (MgO/C), MgO/Al2O3, and MgO/ZrO2, were prepared by the impregnation of MgO to different supporting materials, C, Al2O3, and ZrO2, respectively. Activities of the three MgO-impregnated catalysts were compared with 1:5 of feedstock to catalyst ratio. MgO/C produced the highest quality oil, which consisted of a large amount of aromatic hydrocarbons during the catalytic pyrolysis (CP) of cellulose. When the MgO catalysts were applied to CCP, the selectivity to aromatic hydrocarbons over MgO/C were 13.42%, which were also much higher than those over the other catalysts, including bulk MgO, demonstrating the effectiveness of the MgO/C catalyst on aromatics formation. Importantly, the experimental BTEXs (benzene, toluene, ethylbenzene, xylenes) yields of CCP over MgO/C were also much higher than the theoretical yields, highlighting the effectiveness of hydrogen-rich LLDPE on the CP of cellulose over MgO/C. Further investigation of the cellulose/LLDPE mixing ratio showed that the amount of BTEXs during the CCP of cellulose and LLDPE could be maximized by adjusting the cellulose to LLDPE mixing ratio to 25:75.
Keywords: Acid-base property; Ambient pressures; Catalytic pyrolysis; Copyrolysis; Impregnated catalysts; Ionization detectors; Supporting material; Theoretical yield; Catalytic co-pyrolysis; Cellulose; LLDPE; MgO; MgO/C